Odgovorna organizacija: (konferenčni zbornik) / 36. mednarodna konferenca o razvoju organizacijskih znanosti, (22.-24. marec 2017, Portorož, Slovenija) (University of Maribor Press, 2017)
Responsible Organization, 36th International Conference on Organizational Science Development, Slovenia, Portorož, March 22-24, 2017, (Conference Proceedings). The conference on Organizational Sciences Development is a conference with the longest tradition at the University of Maribor. Each year, the conference brings together students, researchers, businessmen and public administration representatives, who are active in the area of organization and management. The theme of this year’s 36th international conference on Organizational Sciences Development is Responsible Organization referring to the wideness of an organization in its internal and external environment. The responsibility of the organization towards its employees, mission, strategy, processes, technology, and development are just a few areas in which the organization needs to follow the principles of responsibility. The identity of the organization is recognized through its versatile responsible activities, showing its value externally to the customers or recipients of the services offered by the organization. The concurrent mixture of technological and social progress influences individuals as well as the society. The impact of the organization is therefore not only local but global, making a mark on the international level. With this conference theme, we are opening new questions and seeking answers which could contribute to the progress of organizational sciences. Material influence, communications, knowledge, fairness, and nevertheless the ideal of responsible behaviour can be seen as influential factors which can contribute to occasional turbulent situations inside and outside our organizations. Since we are all caught up in moulded mind-sets, not following our experiences anymore, our wish was to keep up with the times and identify best practices, form new methods, and become familiar with the contemporary trends in organizations.